Artificial Intelligence, a Powerful Battering Ram in the Disinformation Industry - Islas, Octavio; Gutiérrez, Fernando; Arribas, Amaia (New Explorations, 2024)
The objective of this article is to analyze how the disinformation industry, understood as organized and systematic practices aimed at disseminating false information with the aim of manipulating public perception, has eroded trust in information, especially with the collaboration of socio-digital networks and artificial intelligence (AI).Technological advances amplify the speed and sophistication with which disinformation spreads, making it difficult to identify and counteract false information, which could be identified with adequate digital literacy. With the use of algorithms and big data analysis, AI is used to personalize political messages, segment audiences and predict electoral trends, seeking not only to persuade voters, but also to create an immersive and emotionally attractive narrative. To do this, the article shows cases of deceiving the audience by presenting false information in a realistic way.Thanks to the formidable development of AI and the advent of synthetic humans, we are witnessing the profound transformation of the entertainment industry and, shortly, political marketing.